Não é escola, é casa!? A pedagogia da alternância nas casas familiares rurais do Sudoeste do Paraná - Plein, Ivonete Terezinha Tremea (2013)
With the purpose of creating strategies for strengthening and preservation of family farms, farmers southwestern Paraná, supported by local leaders, inspired by French initiatives, implemented the Rural Family Houses as a form of education possible to improve the quality of life in agriculture, offering their children a proper education, based on their reality and to come to meet their needs by providing their children the prospect of remaining in rural areas, fully exercising their citizenship and work with dignity. Understanding this model is important, since the Rural Family Houses have spread throughout Brazil as a strategy for rural development, keeping the bond with the land and local culture, while at the same time offering training for young farmers through their realities. Therefore, the aim of this research was to investigate the possibilities and limitations of Teaching through the Pedagogy of Alternation in Rural Family Houses in Paraná (the Regional I ARCAFAR-SUL) in the current period. The research methods used were a literature review, secondary data analysis and field research (documents and questionnaires). As main conclusions highlight that: the Pedagogy of Alternation can be a major contribution to the integral formation, making an effort in the different situations that education somehow need to be more specific, where the local reality can be considered in their wisdom and life experiences exploited as subsidies for vocational training and human. In these places, like the communities of family farmers, the Pedagogy of Alternation makes a difference. Their specific methodological principles and foundations contribute to human development and the environment, thus achieving its two main objectives. However, it is not the solution to all problems of education everywhere. It is unique to specific places, as it has been to the Southwest of Paraná.